Evolution of Type 2 Diabetes Management from a Glucocentric Approach to Cardio-Renal Risk Reduction: The New Paradigm of Care - Jacob, Stephan; Krentz, Andrew J.; Deanfield, John; Rydén, Lars (Drugs (New York, N.Y.), 2021)
For many years, clinical studies could not show that lowering glucose in patients with type 2 diabetes leads to better macrovascular outcomes. In the past few years, new data have shown that treatment with two classes of dugs developed as “glucose-lowering agents,” SGLT2 inhibitors and GLP-1 receptor agonists, can reduce macrovascular and renal complications. These studies have prompted debate about the main aim of type 2 diabetes management. In this review, three eras of diabetes management are described according to the treatment recommendations, such as the ADA/EASD consensus, moving from a pure glucocentric view into the present cardio-renal outcome-oriented approach, this has been endorsed by major diabetes and cardiology societies. While in the first era normalizing HbA 1c was the only focus (e.g., UK Prospective Diabetes Study), failing to show a reduction in cardiovascular morbidity and mortality, further studies analyzing the pros and cons of intensified control such as ACCORD, VADT, ADVANCE recognized that treatment intensification was associated with weight gain and hypoglycemia, thereby potentially reducing the benefits of glycemic control. Therefore, the focus in the second area was on controlling HbA 1c without these unwanted effects. The consistent beneficial results of several cardiovascular outcome trials with SGLT2 inhibitors and GLP-1 receptor agonists showing significantly improved cardio-renal outcomes, induced a paradigm shift: a change from (only) control of HbA 1c to an organ-protective approach with the main focus now on cardio-renal risk; this is now considered as the third era. Recent data indicating beneficial effects of glucose-lowering agents in particular SGLT2 inhibitors even in subjects without diabetes, improving hospitalization for heart failure and renal outcomes might reveal another new era, which could then be considered a fourth era. While current international guidelines call for this paradigm shift, registry data show that we are still far from translating this objective into real-world practice.